Aberrant Drug‐Related Behaviors: A Qualitative Analysis of Medical Record Documentation in Patients Referred to an HIV/Chronic Pain Clinic. Issue 10 (19th August 2014) - Merlin, Jessica S.; Turan, Janet M.; Herbey, Ivan; Westfall, Andrew O.; Starrels, Joanna L.; Kertesz, Stefan G.; Saag, Michael S.; Ritchie, Christine S.
Abstract Background Due to rising rates of opioid addiction and overdose among individuals on chronic opioid therapy, aberrant drug‐related behaviors (ADRBs) are an important and challenging issue. Our objective was to qualitatively investigate the documentation of ADRBs in the medical record. Methods Manually abstracted provider notes from an HIV primary care clinic were analyzed using content analysis methods. Results Categories of ADRBs identified included patients requesting opioids, obtaining nonprescribed opioids, and becoming emotional about opioids. We also identified several types of provider language used when documenting ADRBs, including purely descriptive language and emotional language such as labeling, frustration, and concern, and responses such as setting conditions for opioid prescription and action‐oriented language. Conclusions The impact of including emotional language in the medical record is unknown. Development of instruments that can be used to facilitate ADRB documentation, as well as evidence‐based approaches to addressing ADRBs, is needed.